Complexation of C6-Ceramide with Cholesteryl Phosphocholine – A Potent Solvent-Free Ceramide Delivery Formulation for Cells in Culture - Sukumaran, Pramod; Lönnfors, Max; Långvik, Otto; Pulli, Ilari; Törnquist, Kid; Slotte, J. Peter (PloS one, 2013)
Ceramides are potent bioactive molecules in cells. However, they are very hydrophobic molecules, and difficult to deliver efficiently to cells. We have made fluid bilayers from a short-chain D-erythro-ceramide (C6-Cer) and cholesteryl phosphocholine (CholPC), and have used this as a formulation to deliver ceramide to cells. C6-Cer complexed with CholPC led to much larger biological effects in cultured cells (rat thyroid FRTL-5 and human HeLa cells in culture) compared to C6-Cer dissolved in dimethyl sulfoxide (DMSO). Inhibition of cell proliferation and induction of apoptosis was significantly more efficient by C6-Cer/CholPC compared to C6-Cer dissolved in DMSO. C6-Cer/CholPC also permeated cell membranes and caused mitochondrial Ca(2+) influx more efficiently than C6-Cer in DMSO. Even though CholPC was taken up by cells to some extent (from C6-Cer/CholPC bilayers), and was partially hydrolyzed to free cholesterol (about 9%), none of the antiproliferative effects were due to CholPC or excess cholesterol. The ceramide effect was not limited to D-erythro-C6-Cer, since L-erythro-C6-Cer and D-erythro-C6-dihydroCer also inhibited cell priolifereation and affected Ca(2+) homeostasis. We conclude that C6-Cer complexed to CholPC increased the bioavailability of the short-chain ceramide for cells, and potentiated its effects in comparison to solvent-dissolved C6-Cer. This new ceramide formulation appears to be superior to previous solvent delivery approaches, and may even be useful with longer-chain ceramides.